Manajerial Kepala Sekolah dalam Meningkatkan Kemampuan Menulis Penelitian Tindakan Kelas (PTK) Guru - Umi Awaliatul Laely; Suklani (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
Classroom Action Research is research conducted among teachers to solve a problem in the classroom in order to improve the quality of learning. This requires the role of the school principal to encourage teachers' abilities in conducting Classroom Action Research. This research aims to determine the ability of teachers to write Classroom Action Research, the school principal's efforts to improve teachers' writing skills in creating Classroom Action Research and to find out the inhibiting and supporting factors. The method used in this research is qualitative with a descriptive nature. The subjects in this research were school principals and teachers at SD Negeri Ciduwet 2 Brebes Regency, using interview, observation and documentation data collection techniques. Meanwhile, to analyze data by collecting data, reducing data, presenting data and drawing conclusions. From this research, the results showed that the teacher's ability to write Class Action Research at SD Negeri Ciduwet 2 Brebes Regency was still low and the managerial work carried out by the principal at SD Negeri Ciduwet 2 Brebes Regency in improving the teacher's ability to write Class Action Research had not been implemented optimally. And the inhibiting factors were found, namely the lack of encouragement from the government in educational units, the teacher's motivation was only for promotion and considering Classroom Action Research to be difficult, while the supporting factors for writing Classroom Action Research were the school principal providing opportunities for teachers to develop competence independently through training.